Culture espace history : proceedings of the eleventh biennial conference of the Inernational Association for the Study of People and their Physical Surroundings Middle East Technical University Ankara, Turkey, July 8-12, 1990 : program and abstracts = Culture espace histoire : programme et resumes (Ankara)
xxvii, 291 s.